Understanding Pore Rearrangement during Mild to Hard Transition in Bilayered Porous Anodic Alumina Membranes - Santos, Abel; Montero-Moreno, Josep M.; Bachmann, Julien; Nielsch, Kornelius; Formentin, Pilar; Ferre-Borrull, Josep; Pallares, Josep; Marsal, Lluis F. (ACS Applied Materials and Interfaces, 2011)
We present a systematic study about the influence of the main anodization parameters (i.e., anodization voltage ramp and hard anodization voltage) on the pore rearrangement in nanoporous anodic alumina during mild to hard anodization regime transition. To cover the ranges between mild and hard regimes, the anodization parameters were each set to three levels (i.e., 0.5, 1.0, and 2.0 V s(-1) for the anodization voltage ramp and 80, 110, and 140 V for the hard anodization voltage). To the best of our knowledge, this is the first rigorous study about this phenomenon, which is quantified indirectly by means of a nickel electrodeposition. It is found that pore rearrangement takes place in a relatively random manner. Large areas of pores remain blocked when the anodization regime changes from mild to hard and, under certain anodization conditions, a pore branching takes place based on the self-ordering mechanism at work during anodization. Furthermore, it is statistically demonstrated by means of a design of experiments strategy that the effect of the anodization voltage ramp on the pore rearrangement is practically negligible in contrast to the hard anodization voltage effect. It is expected that this study gives a better understanding of structural changes in nanoporous anodic alumina when anodization is switched from mild to hard regime. Furthermore, the resulting nanostructures could be used to develop a wide range of nanodevices (e.g., waveguides, 1D photonic crystals, Fabry-Perot interferometers, hybrid mosaic arrays of nanowires).
Keywords: alumina bilayers; pore rearrangement; self-ordering mechanism; anodization regime; electrodeposition